The Impact of Digital Cultural Transformation on Elementary School Students' Identity in the Era of Globalization - Hasmawati, Hasmawati; Djumat, Irwan; Rajaloa, Nani I. (Universitas Pendidikan Indonesia, 2025)
The limited understanding and use of social media by teachers and parents in shaping elementary school students has negatively affected local cultural values and character development. Studying the use of social media among elementary school students is therefore urgent, as it can influence self-perception, cultural identity, and potential future risks. The purpose of this study is to analyze the direct impact of social media on the formation of student identity and to identify the factors that support the effective management of social media use in elementary education settings. This research employed a quantitative survey approach with a sample of 360 respondents. Data were collected through a Likert-scale questionnaire ranging from 1 (Strongly disagree) to 5 (Strongly agree). The data were analyzed using descriptive statistics and linear regression with SPSS Version 29.0. The findings revealed that social media use significantly influences children’s perceptions of identity and local culture, highlighting the role of intensive supervision by teachers and parents as well as the importance of integrating digital literacy into learning materials. In conclusion, digital literacy and active environmental involvement have a positive impact on the character development of elementary school students. The practical implication is that digital literacy training within the school environment supports students in forming a positive cultural identity.